Evaluating the Clinical Outcome of Kalium Asrsenicosum in Tinea Cruris - A Case Report (Homoeopathy for All, 2026)
Introduction: Tinea cruris refer to the dermatophytic infection of inguinal folds. Tinea cruris classically presents as annular plaques with raised borders and central hyperpigmentation. Tinea cruris usually occurs in males and hot, humid weather, tight fitting clothes, increased sweating, maceration and diabetes are important risk factors. These are not classical sexually transmitted infections, but by virtue of prolonged and intimate direct contact during sexual intercourse, they can potentially be transferred from infected patients to their partners. Case Summary: A case of tinea cruris in a 20-year-old male patient is reported, which was effectively treated with homoeopathic medicine. Based on the totality of symptoms, the homoeopathic medicine Kalium arsenicosum in 30 C potency was prescribed as the first dose and improvement was observed in subsequent follow-ups. The outcome was assessed through before-and after-treatment photographs. The case has been reported as per HOM CASE guidelines. This evidenced based case suggests that tinea cruris can be successfully managed with individualised homoeopathic treatment.
Keywords: Kalium arsenicosum, Tinea cruris, Ringworm, Fungal infection, Dermatophyte infection